Patient-specific computational fluid dynamics analysis of transcatheter aortic root replacement with chimney coronary grafts. (29th November 2020) - Conti, Michele; Romarowski, Rodrigo M; Ferrarini, Anna; Stochino, Matteo; Auricchio, Ferdinando; Morganti, Simone; Segesser, Ludwig Karl von; Ferrari, Enrico
Abstract: OBJECTIVES: Transcatheter aortic root repair (TARR) consists of the simultaneous endovascular replacement of the aortic valve, the root and the proximal ascending aorta. The aim of the study is to set-up a computational model of TARR to explore the impact of the endovascular procedure on the coronary circulation supported by chimney grafts. METHODS: Computed tomography of a patient with dilated ascending aorta was segmented to obtain a 3-dimensional representation of the proximal thoracic aorta, including aortic root and supra-aortic branches. Computed assisted design tools were used to modify the geometry to create the post-procedural TARR configuration featuring the main aortic endograft integrated with 2 chimney grafts for coronary circulation. Computational Fluid Dynamics simulations were run in both pre- and post-procedural configurations using a pulsatile inflow and lumped parameter models at the outflows to simulate peripheral aortic and coronary circulation. Differences in coronary flow and pressure along the cardiac cycle were evaluated. RESULTS: After the virtual implant of the TARR device with coronary grafts, the flow became more organized and less recirculation was seen in the ascending aorta. Coronary perfusion was guaranteed with negligible flow differences between pre- and post-procedural configurations. However, despite being well perfused by chimney grafts, the procedure induces an increase of the pressure drop between the coronary ostia and the ascending aorta of 8 mmHg. CONCLUSIONS: The proposed numerical simulations, in the specific case under investigation, suggest that the TARR technique maintains coronary perfusion through the chimney grafts. This study calls for experimental validation and further analyses of the impact of TARR on cardiac afterload, decrease of aortic compliance and local pressure drop induced by the coronary chimney grafts.